2021
DOI: 10.1111/1365-2745.13599
|View full text |Cite
|
Sign up to set email alerts
|

Local‐scale climatic refugia offer sanctuary for a habitat‐forming species during a marine heatwave

Abstract: Gradual climate change and discrete extreme climatic events have driven shifts in the structure of populations and the distribution of species in many marine ecosystems. The most profound impacts of recent warming trends have been generally observed at species' warm edges and on large conspicuous species. However, given that different species and populations exhibit different responses to warming, and that responses are highly variable at regional scales, there is a need to broaden the evidence to include less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 117 publications
2
53
0
Order By: Relevance
“…In addition, human overexploitation of top predators of sea urchins (e.g., the sparid fishes Diplodus sargus and D. vulgaris (Guidetti, 2004), has reduced the control over this component, thus leading to sea urchin overgrazing on algal forests, creating barrens (Ling et al, 2015). In addition, disruption of climatic patterns with more frequent and stronger storm events, as well as heat waves, which are becoming increasingly frequent during summer in the whole Mediterranean Sea (Darmaraki et al, 2019), are expected to have severe effects at local scales on fragmented populations of fucalean species (Verdura et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, human overexploitation of top predators of sea urchins (e.g., the sparid fishes Diplodus sargus and D. vulgaris (Guidetti, 2004), has reduced the control over this component, thus leading to sea urchin overgrazing on algal forests, creating barrens (Ling et al, 2015). In addition, disruption of climatic patterns with more frequent and stronger storm events, as well as heat waves, which are becoming increasingly frequent during summer in the whole Mediterranean Sea (Darmaraki et al, 2019), are expected to have severe effects at local scales on fragmented populations of fucalean species (Verdura et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, such as regimes of exposure to air and nutrient availability are pivotal for mediolittoral and upper infralittoral assemblages respectively. Catastrophic events such as huge storms or thermal anomalies also regularly shape shallow assemblages (e.g., Navarro et al, 2011;Verdura et al, 2021). Amongst top-down processes, overgrazing by sea urchins such as Paracentrotus lividus and Arbacia lixula (but also by herbivorous fishes, see paragraph 2.2), could strongly reduce algal biomass, availability and export of algal detritus, and simplify the associated community structure (Sala et al, 1998;Sala et al, 2012;Yeruham et al, 2020).…”
Section: Mediolittoral and Infralittoral Zonementioning
confidence: 99%
“…Various studies have shown that macroalgae, especially canopyforming species, are threatened by rising temperatures (Smale, 2020). Furthermore, marine heatwaves have also shown significant impacts on coastal macroalgal formations (Frölicher and Laufkötter, 2018;Filbee-Dexter et al, 2020;Verdura et al, 2021). These extreme events are likely given the projected climate change scenarios (Filbee-Dexter et al, 2020).…”
Section: Climate Change-related Effects Ocean Warmingmentioning
confidence: 99%